Pengaruh Penambahan Nitrogen dengan Konsentrasi yang Berbeda terhadap Laju Pertumbuhan Rumput Laut Caulerpa racemosa var. uvifera - Budiyani, Felycia Belri; Suwartimah, Ken; Sunaryo, Sunaryo (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Caulerpa racemosa is a type of seaweed that has potentially to be cultivated because very popular and liked by most peoples. Japan and Philipines made the C. racemosa as one of the aquaculture commodities. C. racemosa culturing has not been done in Indonesia. Usually people just take directly from nature thus diminishing its presence in nature. Seaweed farming important to be done to inhance the production of seaweed. This study was conducted in May - July 2011 in a wet lab, University of Diponegoro Marine Station Teluk Awur, Jepara. The research method used an experimental method with a completely randomized design. This study used four treatments and one control, each of which was repeated three times. Rearing media using sea water plus nitrogen with different concentrations, namely: A (0 μM), B (50 μM), C (100 μM), D (150 μM) and E (200 μM). The results showed that the addition of urea nitrogen was significant difference on the growth of C. racemosa var. uvifera (p <0.01). The average of weight gain of C. racemosa var. uvifera for 42 days, as follows: A = 3.38 ± 0.089 g, B = 3.46 ± 0.14 g; C = 3.59 ± 0.18 g; D = 3.44 ± 0.11 g and E = 3.42 ± 0.10 g. Specific growth rate of C. racemosa var. uvifera generated during the study, namely: A 0.60 ± 0.015 % per day; B of 0.94 ± 0.012% per day; C of 1.36 ± 0.024% per day; D of 0.84 ± 0.026% per day and E of 0.75 ± 0.028% per day. The lowest specific growth rate of C. racemosa var. uvifera was reached on the treatment of A and the highest in the treatment of C.